Information service quality and destination security as predictors of tourists’ quality of life: the mediating role of tourist satisfaction - Marta Widian Sari; Vivi Nila Sari (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
Although prior tourism research has examined service quality, destination security, and tourist satisfaction separately, limited studies have structurally integrated these variables to explain tourists’ quality of life, particularly in secondary urban destinations. Drawing on service quality and well-being perspectives, this study examines the mediating role of tourist satisfaction in linking information service quality and destination security to tourists’ quality of life in Bukittinggi. Data were collected through an online survey using purposive sampling, involving 70 respondents who had previously visited Bukittinggi. The measurement model met validity and reliability criteria (AVE > 0.50; CR > 0.70). Structural relationships were analyzed using PLS-SEM with bootstrapping. The results show that information service quality significantly affects tourist satisfaction (β = 0.204, p < 0.05) and quality of life (β = 0.215, p < 0.05), while destination security significantly influences satisfaction (β = 0.732, p < 0.001) but not quality of life directly. The model explains 81.1% of the variance in satisfaction and 82.0% in quality of life. Mediation analysis confirms that tourist satisfaction fully mediates the effect of destination security and partially mediates the influence of information service quality. These findings underscore the role of satisfaction as a mechanism translating service and security perceptions into well-being outcomes. However, the small non-probability sample and self-reported data may limit generalizability.